1989
DOI: 10.1002/zoo.1430080506
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of oocytes retrieved from stimulated and unstimulated ovaries of pig-tailed macaques (Macaca nemestrina) as a model to enhance the genetic diversity of captive lion-tailed macaques (Macaca silenus)

Abstract: Steroid hormone levels were measured during unstimulated menstrual cycles of pig-tailed macaques (Mucucu nemestrina) and lion-tailed macaques (Mucucu silenus). The values were similar, suggesting that the pig-tailed macaque may be an appropriate model for in vitro fertilization and embryo transfer in the lion-tailed macaque.Two follicular stimulation protocols were compared to evaluate the yield and quality of the oocytes obtained from pig-tailed macaques. Five animals received a regimen of PMSG (Protocol I) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Among the several types of media reported, my research group selected TYH medium [103], which was developed for IVF of mouse eggs. Furthermore, by incubation of the spermatozoa in medium that contained caffeine and dibutyryl cyclic AMP, sperm capacitation and hyperactivated motion were induced in spermatozoa of the rhesus monkey (Macaca mulatta) [11], the pig-tailed monkey (Macaca nemestrina) [18], and the cynomolgus monkey [5,56]. Our study also confirmed this finding in cynomolgus monkeys [84], Japanese monkeys [83], and African green monkeys (Cercopithecus aethiops) [78].…”
Section: Sperm Quality In Vivo and In Vitrosupporting
confidence: 83%
“…Among the several types of media reported, my research group selected TYH medium [103], which was developed for IVF of mouse eggs. Furthermore, by incubation of the spermatozoa in medium that contained caffeine and dibutyryl cyclic AMP, sperm capacitation and hyperactivated motion were induced in spermatozoa of the rhesus monkey (Macaca mulatta) [11], the pig-tailed monkey (Macaca nemestrina) [18], and the cynomolgus monkey [5,56]. Our study also confirmed this finding in cynomolgus monkeys [84], Japanese monkeys [83], and African green monkeys (Cercopithecus aethiops) [78].…”
Section: Sperm Quality In Vivo and In Vitrosupporting
confidence: 83%
“…In contrast, there is a species specificity for primate LH in follicle/ oocyte maturation and ovulation (Knobil et al, 1959;van Wagenen, 19681, since LH-CG receptors in monkeys (Cameron and Stouffer, 1981) and humans (Berman and Sairam, 1983) have a much higher affinity for primate, as compared to nonprimate gonadotropins. Thus, it is possible to stimulate the growth of numerous follicles in macaques by a PMSG regimen beginning around day 3-5 of the cycle, followed on day 16 by a primate LH-like preparation (hCG) for ovulatory maturation (Bavister et al, 1983Boatman et al, 1986;Cranfield et al, 1989;Fujisaki et al, 1989). Nevertheless, problems addressed in the section on limitations restrict this protocol's usefulness, particularly in endangered species.…”
Section: Pregnant Mare Serum Gonadotropin (Pmsg)mentioning
confidence: 99%
“…Variable-dose, individualized regimens of gonadotropins, presently common in clinical IVF-ET programs (Jones, 19851, were employed 20 years ago to induce single ovulations in bonnet mon- keys (Ovadia et al, 1971). Recent results, although preliminary, suggest that individualized protocols could aid in achieving a greater incidence of hyperstimulation and the desired numbers of oocytes in nonhuman primates (Cranfield et al, 1989). Since hMG preparations contain both FSH-and LHactivity, both gonadotropins may be promoting the growth and maturation of multiple follicles.…”
Section: Human Gonadotropinmentioning
confidence: 99%
See 2 more Smart Citations